Genetic conjugation of components in two pneumococcal fusion protein vaccines enhances paediatric mucosal immune responses. Issue 14 (30th March 2015) - Pope, Caroline; Oliver, Elizabeth H.; Ma, Jiangtao; Langton Hewer, Claire; Mitchell, Tim J.; Finn, Adam
Highlights A new, affordable pneumococcal vaccine offering broader protection is needed. Fusion of PsaA to Δ6Ply enhances CD4+ T-cell responses in children's nasopharynges. CD4+ T-cell responses had a Th1/Th17 cytokine profile. Membrane binding activity of Ply/Δ6Ply may confer valuable adjuvant properties. Non-toxic pneumolysoids may be suitable for inclusion in future vaccines.